Induction of Terpene Biosynthesis in Berries of Microvine Transformed with VvDXS1 Alleles - Dalla Costa, Lorenza; Emanuelli, Francesco; Trenti, Massimiliano; Moreno-Sanz, Paula; Lorenzi, Silvia; Coller, Emanuela; Moser, Sergio; Slaghenaufi, Davide; Cestaro, Alessandro; Larcher, Roberto; Gribaudo, Ivana; Costantini, Laura; et al. (Frontiers in Plant Science, 2018)
Terpenoids, especially monoterpenes, are major aroma-impact compounds in grape and wine. Previous studies highlighted a key regulatory role for grapevine 1-deoxy-D-xylulose 5-phosphate synthase 1 (VvDXS1), the first enzyme of the methylerythritol phosphate pathway for isoprenoid precursor biosynthesis. Here, the parallel analysis of VvDXS1 genotype and terpene concentration in a germplasm collection demonstrated that VvDXS1 sequence has a very high predictive value for the accumulation of monoterpenes and also has an influence on sesquiterpene levels. A metabolic engineering approach was applied by expressing distinct VvDXS1 alleles in the grapevine model system ‘microvine’ and assessing the effects on downstream pathways at transcriptional and metabolic level in different organs and fruit developmental stages. The underlying goal was to investigate two potential perturbation mechanisms, the former based on a significant over-expression of the wild-type (neutral) VvDXS1 allele and the latter on the ex-novo expression of an enzyme with increased catalytic efficiency from the mutated (muscat) VvDXS1 allele. The integration of the two VvDXS1 alleles in distinct microvine lines was found to alter the expression of several terpenoid biosynthetic genes, as assayed through an ad hoc developed TaqMan array based on cDNA libraries of four aromatic cultivars. In particular, enhanced transcription of monoterpene, sesquiterpene and carotenoid pathway genes was observed. The accumulation of monoterpenes in ripe berries was higher in the transformed microvines compared to control plants. This effect is predominantly attributed to the improved activity of the VvDXS1 enzyme coded by the muscat allele, whereas the up-regulation of VvDXS1 plays a secondary role in the increase of monoterpenes.